The Effect of Vitamin E Supplementation on the Histopathological Changes of The Hearts Mice Given High Fat Diet - Daud, Razali (Jurnal Kedokteran Hewan, 2007)
The aim of this study was to determine the protective effect of vitamin E on mice heart. Twentyfivemalemiceweighing40gattheageof3monthswereused.Themicewereadaptedforaweekandfedbasaldiet.Themicewerefednormaldietascontrol(group1),highfat+50IUVitaminE(groupII);highfat + 100 IU Vitamin E (group III) high fat + 200 IU Vitamin E (group IV); high fat + 400 IUVitamin E (Group V). Diet was given about 10% body weight, water was given ad libitum every day. After 3 months, all animal were then killed. The hearts were collected for routine histopathologicalexamination. The result indicate that lesions in the heart consist of swollen eosinophilic hyalinization ofcytoplasm, vacuolization, and necrosis myocardium (cardiomiopathy) in all mice receiving high fat dietwith less than 400 IU Vitamin E.Keywords: high fat diet, vitamin E, cardiovascular diseases